1952
DOI: 10.1038/icb.1952.19
|View full text |Cite
|
Sign up to set email alerts
|

Lower Fatty Acids in the Intermediary Metabolism of Sheep

Abstract: Acetic, propionic and butyric acids which ai'e formed by bacterial fermentation in the paunch of ruminants assume an import^aiit role in the metabolism of these animals (Marston, 1939(Marston, , 1948 PhiUipson, 1947 PhiUipson, , 1948. Although the greater part of the energy requirements of the sheep are met by lower fatty acids which arise in this way by microbial dissimilation of carbohydrates, the capacity of the individual acids to provide useful energy to the animal probably differs widely (Marston, 1948)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1954
1954
1972
1972

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 7 publications
(14 reference statements)
2
6
0
Order By: Relevance
“…Jarrett, Potter & Filsell (1952), Johnson (1955) (1955) have shown that the rumen epithelium is a major site for the conversion of butyric acid to ketone bodies. The finding of a smaller, but nevertheless significant, rise in blood ketones with acetic acid is in agreement with the results of Jarrett & Potter (1950), Jarrett et al (1952) and Clark & Malan (1956). All the above-mentioned workers have demonstrated the antiketogenic nature of propionic acid.…”
Section: Steam-volatile Fatty-acid Metabolism 255supporting
confidence: 82%
“…Jarrett, Potter & Filsell (1952), Johnson (1955) (1955) have shown that the rumen epithelium is a major site for the conversion of butyric acid to ketone bodies. The finding of a smaller, but nevertheless significant, rise in blood ketones with acetic acid is in agreement with the results of Jarrett & Potter (1950), Jarrett et al (1952) and Clark & Malan (1956). All the above-mentioned workers have demonstrated the antiketogenic nature of propionic acid.…”
Section: Steam-volatile Fatty-acid Metabolism 255supporting
confidence: 82%
“…The concentration of pyruvate in the blood of normal rabhits was found to agree closely with that reported previously (Lu, 1939), but the normal value for adult sheep was found to he much lower than that observed hy Austin (1947). However, this difference might well he attributed to the different experimental conditions, as it is clear that a state of activity affects the pyruvate concentration in the hlood: to obtain reasonably comparable results it is essential that the animal be maintained in a thoroughly placid condition (Jarrett, Potter and Filsell, 1952). The technique of intravenous cannulation used in this study assisted considerably towards this end.…”
Section: Resultssupporting
confidence: 73%
“…which resulted in an average rise of 4 mg./lOO ml. No alteration followed an injection of sodium acetate (Jarrett, Potter and Filsell, 1952).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VFA concentrations in whole blood were estimated by the method of Jarrett, Potter and Filsell (1952), using phenol red to detect the end-point of titration.…”
Section: Methodsmentioning
confidence: 99%